(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article deals with a problem of professional training of future military personnel. The author shows the necessity of developing professional knowledge, skills and abilities, as well as courage, ability to fulfill orders, discipline, self-control and dedication, which are regarded as an obligatory component of the professional training in higher military educational institutions. The effectiveness of professional activities of military personnel is determined by a system of socio-psychological, technical, medical and biological, as well as special military skills.